2.5k views
0 votes
Find (f/g)(x)

A
B
C
D

Find (f/g)(x) A B C D-example-1
User Anil Sidhu
by
5.2k points

2 Answers

4 votes

Answer:

Choice a is correct answer.

Explanation:

We have given two function.

f(x) = √x²-1

g(x) = √x-1

We have to find the quotient of given functions.

(f/g)(x) = ?

The formula to find quotient of two function:

(f/g)(x) = f(x) / g(x)

Putting given values in above formula, we have

(f/g)(x) = √x²-1 / √x-1

(f/g)(x) = √(x-1)(x+1) / √x-1

(f/g)(x) = √x-1√x+1 / √x-1

(f/g)(x) = √x+1 which is the answer.

User Matt Westlake
by
5.0k points
7 votes

Answer:

Option (a) is correct.


(f(x))/(g(x))=√(x+1)

Explanation:

Given :
f(x)=√(x^2-1) and
g(x)=√(x-1)

We have to find the value of
((f)/(g))(x)

Consider
((f)/(g))(x)

It is same as
((f)/(g))(x)=(f(x))/(g(x))

Substitute the value of f(x) and g(x) , we have,


(f(x))/(g(x))=(√(x^2-1))/(√(x-1))

Combining same powers ,
\quad (√(x))/(√(y))=\sqrt{(x)/(y)} , We have,


=\sqrt{(x^2-1)/(x-1)}

Factorize numerator as ,
x^2-1:\quad \left(x+1\right)\left(x-1\right)

We have ,
=(\left(x+1\right)\left(x-1\right))/(x-1)

Cancel out (x-1) , we get, (x + 1)


(f(x))/(g(x))=√(x+1)

Thus, Option (a) is correct.

User Krunal Limbad
by
5.2k points